2012
DOI: 10.1128/aac.05354-11
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Disposition of Tedizolid following Administration of Once-Daily Oral 200-Milligram Tedizolid Phosphate in Healthy Adult Volunteers

Abstract: cThis study assessed the pulmonary disposition of tedizolid, an oxazolidinone, in adult volunteers receiving 200 mg of the prodrug tedizolid phosphate orally every 24 h for 3 days to steady state. Plasma samples were collected over the dosing interval, and participants were randomized to undergo bronchoalveolar lavage (BAL) at 2, 6, 12, or 24 h after the last dose. Drug concentrations in plasma, BAL fluid, and alveolar macrophages (AM) were determined by liquid chromatography-tandem mass spectrometry (LC-MS/MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 29 publications
4
84
1
Order By: Relevance
“…These exposures were comparable to that achieved in humans (109.30 mg · h/liter) following the administration of a 200-mg once-daily (QD) clinical dose. However, due to the differences in the tedizolid penetration ratios in mice and humans, the mean plasma fAUC 0 -24 achieved in mice with these doses were higher than that achieved in humans following a clinical dose (13). The ELF exposures of tedizolid in human and mouse models are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These exposures were comparable to that achieved in humans (109.30 mg · h/liter) following the administration of a 200-mg once-daily (QD) clinical dose. However, due to the differences in the tedizolid penetration ratios in mice and humans, the mean plasma fAUC 0 -24 achieved in mice with these doses were higher than that achieved in humans following a clinical dose (13). The ELF exposures of tedizolid in human and mouse models are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The discrepancy in the findings between our study and Drusano et al could be attributed, at least in part, to the difference in the infection model utilized. Tedizolid shows substantial accumulation in the lung epithelium, as evidenced by its high ELF penetration ratio both in humans and in mice (13,14), which could account for its enhanced activity against lung infections through the direct effect of the drug even if the host immune defenses were suppressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another key difference between the current and previous studies is the infection site. One intuitive theory to explain the discrepancy is the differential penetration of the oxazolidinones into the lung infection site (12,16,24,26,55 (26). This PK difference at the infection site is a plausible explanation for the lower PD targets for oxazolidinones in pulmonary models compared to soft tissue models.…”
Section: Discussionmentioning
confidence: 99%
“…12,[20][21][22] Measurement of unbound concentrations in the ELF is likely to best describe antibiotic activity, particularly for highly protein bound antibiotics. In a prospective PK study of 13 critically ill patients with ventilator-associated pneumonia (VAP) treated with teicoplanin ( > 85% protein binding), the median unbound teicoplanin concentrations in blood and ELF were similar, 21 which suggested that the unbound fraction of drug penetrated well into the lung tissue.…”
Section: Protein Bindingmentioning
confidence: 99%